ANALISIS BAKTERI Escherichia coli PADA MAKANAN SIAP SAJI DI KANTIN RUMAH SAKIT X DAN KANTIN RUMAH SAKIT Y: Analysis of Escherichia coli Bacteria on Fast Food at hospital X and Y cafetaria - Saridewi, Inggit; Pambudi, Arief; Ningrum, Yulia Fitria (LPPM Universitas Negeri Jakarta, 2016)
The increasing human activity makes the preference for fast food increases. However, some people do not pay attention to the hygiene conditions of food processed from food stalls. Food handlers, equipment utilization, food processing, clean water, and the packaging are the critical points of bacterial contamination. Escherichia coli is a bacterium that usually used as the indicator of food hygiene. The objective of this study is to examine the contamination of coliform bacteria, especially E. coli at two hospital cafeteria by using MPN method and questionnaire regarding the implementation of the basic principles of hygiene. Stages of tests performed that are the presumption test, confirmation test, complementary test, gram stain test, biochemical test IMViC and supported by a questionnaire. From the two locations tested, some samples showed positive result in a presumption test and confirmation test but negatively complementary to biochemical test. This indicates that the sample does not contain E. coli bacteria in food, but there is the possibility of Citrobacter. The negative results of the IMVIC test showed that it is possible bacteria found in the presumption test and confirmation test not E. coli and non-pathogenic bacteria. Based on the results of the questionnaire, most of restaurant owner has understood to served food. Food at the hospital X and Y cafetaria are safe to consume because it has a negative E.coli.